Tombusvirus Y-Shaped Translational Enhancer Forms a Complex with eIF4F and Can Be Functionally Replaced by Heterologous Translational Enhancers - Nicholson, Beth L. (American Society for Microbiology, 2013)
Certain plus-strand RNA plant viruses that are uncapped and nonpolyadenylated rely on RNA elements in their 3′ untranslated region, termed 3′-cap-independent translational enhancers (3′CITEs), for efficient translation of their proteins. Here, we have investigated the properties of the Y-shaped class of 3′CITE present in the tombusvirus Carnation Italian ringspot virus (CIRV). While some types of 3′CITE have been found to function through recruitment of translation initiation factors to the viral genome, no trans-acting translation-related factors have yet been identified for the Y-shaped 3′CITE. Our results indicate that the CIRV 3′CITE complexes with eIF4F and eIFiso4F, with the former mediating translation more efficiently than the latter. In nature, some classes of 3′CITE are present in several different viral genera, suggesting that these elements hold a high degree of modularity. Here, we test this concept by engineering chimeric viruses containing heterologous 3′CITEs and show that the Y-shaped class of 3′CITE in CIRV can be replaced by two alternative types of 3′CITE, i.e., a Panicum mosaic virus-like 3′CITE or an I-shaped 3′CITE, without any major loss in in vitro translation or replication efficiency in protoplasts. The heterologous 3′CITEs also mediated whole-plant infections of Nicotiana benthamiana, where distinct symptoms were observed for each of the alternative 3′CITEs and 3′CITE evolution occurred during serial passaging. Our results supply new information on Y-shaped 3′CITE function and provide insights into 3′CITE virus-host compatibilities.